Análisis de las operaciones reportadas a la inteligencia financiera mexicana (2015)
Mexico´s struggle to identify and fight transactions with illegal proceeds was strengthened by the creation of the Financial Intelligence Unit (FIU) as well as its entry into the South American Financial Action Group (GAFISUD). Between 2004 and 2013 service providers within the Mexican financial system reported transactions that could be related to money laundering. Thus, before the completion of the first year in which the Federal Law of Prevention and Identification of Operations with Resources from Illicit Origins became valid, the aim of this study is to investigate the reports generated by the Mexican Financial Intelligence, to know the number and kind of reports and to learn which Mexican states have higher occurrences. It is of particular interest to find out if the policies used to combat resources from illicit origin are showing a decrease in the information subject to be analysed by the FIU.